Transformation Of Learning Media In Edutainment-Based Mushaf - Imronudin; Arsyad, Faiz (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2024)
The learning media for Al-Qur'an manuscripts in Indonesia has experienced a transformation in the past decade. The birth of this edutainment-based mushaf is proof of technological progress and innovation as well as a symbol of the shift in conventional Al-Qur'an learning media towards digital. It is hoped that this research will provide additional information on the shift in learning media for Al-Qur'an manuscripts in Indonesia from conventional to digital. On the other side, this research wants to strengthen the view that everything in this world, especially those related to learning, requires learning, especially learning the Koran. The research method uses a qualitative method. The approach used is interpretive, namely exploring and analyzing the learning media in Edutainment-based manuscripts